Cloning and expression analysis of HY5 transcription factor gene of safflower in response to light signal. (23rd June 2022) - Xian, Bin; Chen, Chao; Wang, Jie; Chen, Jiang; Wu, Qinghua; Ren, Chaoxiang; Pei, Jin
Abstract: The flower of the safflower ( Carthamus tinctorius L.) is a traditional Chinese medicine that can improve cerebral blood flow due to its enrichment in flavonoids. Light is one of the main environmental factors that affects safflower growth and flavonoid synthesis. Elongated hypocotyl 5 (HY5) plays an important role in plants' light signal transduction. However, no study of HY5 in safflower has been conducted. In this study, a 462‐bp sequence of CtHY5 was successfully cloned. The expression pattern of CtHY5 in different safflower tissues and the expression patterns of CtHY5 and CtCHS1 in full‐blooming flowers that were treated under different light intensities were studied. The subcellular localization and the overexpression of CtHY5 were carried out as well. CtHY5 has a DNA‐binding region belonging to the basic leucine zipper transcription factor family. CtHY5 was specifically expressed in flowers. The expression level of CtHY5 first increased and then decreased with increasing light intensity, which was similar to the expression pattern of CtCHS1 . The subcellular localization study was implemented in safflower protoplasts and the YFP fluorescence was observed in nucleus. The overexpression analysis initially verified the promotion effect of CtHY5 to the expression of CtCHS1 and the content of flavonoids.